Analisis Kemampuan Menulis Melalui Program Literasi “Cara Sakti Hobi Nulis” Di MI Modern Sakti Permatahati Ibu Tulungagung - Sri Saktiani (Balai Diklat Keagamaan Surabaya, 2022)
Literacy skills will be optimally honed if they are introduced from the elementary education level. The important role of literacy skills as an integral part of receiving or disseminating information. So that literacy becomes an important thing that must be understood by someone, especially in order to be able to receive and exchange information properly. The purpose of this study is to analyze the literacy skills of students through the study programs available at MI Modern SAKTI Permatahati IBU Tulungagung. This research method uses a descriptive qualitative approach, with the type of case study research. Data collection techniques using observation, interviews and documentation. The subjects of this study were students of grades IV, V and VI. Data analysis used is data reduction, data presentation and conclusion. The results of the study, there are four important factors that encourage increased literacy of students, namely factors of learning resources, learning materials, learning and evaluation strategies, as well as factors that are directly related to the head of the madrasa, teachers and students as parties who are directly involved with the teaching and learning process that held. The MI Modern SAKTI Permatahati IBU Tulungagung formulates four factors and encourages successful learning by implementing literacy programs as an effort to improve literacy quality.